The Influence Of Web Gratification And Irritation On Online Purchase In Apparel Industry - Ashar, Siti Masitah (2019)
Increasing internet activity and its number of users have strengthened the potency of uses and gratification. The concept of online purchase led the current research to finding that the conceptualisation of online shopping encompasses various aspects of consumer behaviour relating to the action of purchasing products (i.e. buying customize goods and services, collecting information, seeking recommendations, comparing products with several seller, or even browsing for enjoyment). Additionally, it investigates the incorporation of use and gratification theory (UGT) in the online shopping context. This study aims to examine the relationship between informativeness gratifications (IG), entertainment gratifications (EG), web irritation (WI) and cognitive attitude (CA). Furthermore, it attempts to examine the relationship between informativeness gratification (IG), entertainment gratifications (EG), web irritation (WI) and consumer emotions (CE). Besides that, this study attempts to study the relationship between cognitive attitude (CA), consumer emotions (CE) and online purchase. In addition, the influence of cognitive attitude (CA) and consumer emotion (CE) as a mediator between informativeness gratification, entertainment gratification, web irritation and online purchase is included in the integrated framework of this study. By using of the convenience sampling technique and a structured questionnaire via online survey, data was amassed from individual online shoppers whereby 615 responses were collected. However, from these only 465 responses were taken in for further analysis as the remainder were considered incomplete and thus discarded.